Duration of Replication-Competent Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Shedding Among Patients With Severe or Critical Coronavirus Disease 2019 (COVID-19). (6th July 2022) - Kim, Do Young; Lin, Michael Y; Jennings, Cheryl; Li, Haiying; Jung, Jae Hyung; Moore, Nicholas M; Ghinai, Isaac; Black, Stephanie R; Zaccaro, Daniel J; Brofman, John; Hayden, Mary K; ,
Abstract: Background: Patterns of shedding replication-competent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in severe or critical COVID-19 are not well characterized. We investigated the duration of replication-competent SARS-CoV-2 shedding in upper and lower airway specimens from patients with severe or critical coronavirus disease 2019 (COVID-19). Methods: We enrolled patients with active or recent severe or critical COVID-19 who were admitted to a tertiary care hospital intensive care unit (ICU) or long-term acute care hospital (LTACH) because of COVID-19. Respiratory specimens were collected at predefined intervals and tested for SARS-CoV-2 using viral culture and reverse transcription–quantitative polymerase chain reaction (RT-qPCR). Clinical and epidemiologic metadata were reviewed. Results: We collected 529 respiratory specimens from 78 patients. Replication-competent virus was detected in 4 of 11 (36.3%) immunocompromised patients up to 45 days after symptom onset and in 1 of 67 (1.5%) immunocompetent patients 10 days after symptom onset ( P = .001). All culture-positive patients were in the ICU cohort and had persistent or recurrent symptoms of COVID-19. Median time from symptom onset to first specimen collection was 15 days (range, 6–45) for ICU patients and 58.5 days (range, 34–139) for LTACH patients. SARS-CoV-2 RNA was detected in 40 of 50 (80%) ICU patients and 7 of 28 (25%) LTACH patients. Conclusions: Immunocompromise and persistent or recurrent symptoms were associated with shedding of replication-competent SARS-CoV-2, supporting the need for improving respiratory symptoms in addition to time as criteria for discontinuation of transmission-based precautions. Our results suggest that the period of potential infectiousness among immunocompetent patients with severe or critical COVID-19 may be similar to that reported for patients with milder disease. Abstract : Among patients with severe or critical COVID-19, replication-competent SARS-CoV-2 was detected in respiratory specimens of 4/11 (36%) immunocompromised patients up to 45 days after symptom onset and 1/67 (1.5%) immunocompetent patients up to 10 days after symptom onset.